Cogon grass public enemy n°1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
According to a recent study carried out by the International Institute of Tropical Agriculture (IITA) station in Benin, farmers consider cogon grass